Exploring Interactive Read Aloud Literacy Learning and Quality Books in the Merdeka Curriculum: Eksplorasi Pembelajaran Literasi Membaca Nyaring Interaktif dan Buku Berkualitas dalam Kurikulum Merdeka - Durriyah, Tati Lathipatud; Niasari, Catur; Afriyanti , Iin (Universitas Muhammadiyah Sidoarjo, 2024)
The Indonesian government issued a policy on teacher literacy teaching competency standards, which includes teachers' ability to help students access, use, interpret and communicate information and ideas through various texts according to students' characteristics and needs (Ministry of Education, 2022a). This study aims to promote reading aloud and interactive book selection in literacy learning for public primary school teachers in Depok, West Java, Indonesia. This qualitative case study explored teachers' understandings and practices in selecting books and integrating reading aloud activities with learning outcomes in Merdeka Curriculum. Six teachers participated in the study, which involved data collection through surveys, focus group discussions (FGDs), interviews, observations and oral reflections. Using manual thematic data analysis, this study focused on teachers' practices of selecting leveled books and integrating discussions in reading aloud with Learning Outcomes. The results showed that teachers began to express their understanding of book selection. Major themes that emerged included the importance of selecting quality books and the challenges of selecting quality books. In the context of literacy learning, several themes also emerged that became teachers' reflections in conducting interactive read aloud activities in accordance with the learning outcomes, namely; benefits, awareness for better classroom preparation, interactive discussion spaces and continuous training.